2016
DOI: 10.1186/s40792-016-0227-5
|View full text |Cite
|
Sign up to set email alerts
|

Choriocarcinoma syndrome after resection of primary pulmonary choriocarcinoma: report of a case

Abstract: BackgroundChoriocarcinoma syndrome is known as a lethal complication from tumoral hemorrhage, which frequently occurs at the site of tumor metastasis.Case presentationA 59-year-old man with 60-pack-year smoking history was referred to our hospital because of hemoptysis. Chest computed tomography (CT) showed a 28 × 18 mm spiculated nodule with a cavity infiltrating the left upper lobe. A transbronchial lung biopsy was performed, and histopathological examinations revealed adenocarcinoma. No distant or regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
(6 reference statements)
0
16
2
Order By: Relevance
“…In addition, Takahashi et al . reported that they resected lung lesions with choriocarcinoma components, and ARDS occurred 1 month after the resection procedure despite the removal of the primary lesion . These cases suggest that choriocarcinoma syndrome is not simply caused by bleeding from metastatic lesions, but rather might be caused by cytokine release associated with tumor lysis.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, Takahashi et al . reported that they resected lung lesions with choriocarcinoma components, and ARDS occurred 1 month after the resection procedure despite the removal of the primary lesion . These cases suggest that choriocarcinoma syndrome is not simply caused by bleeding from metastatic lesions, but rather might be caused by cytokine release associated with tumor lysis.…”
Section: Discussionmentioning
confidence: 95%
“…CS is more likely with higher levels of bHCG. [7] The most common presentation of CS is pulmonary hemorrhage, but hemorrhage can develop in the liver, brain, and small bowel as well. Hemorrhage can occur immediately following chemotherapy, or present as the initial primary complaint.…”
Section: Discussion and Managementmentioning
confidence: 99%
“…Among the different choriocarcinoma distant recurrence sites, the lung is the most frequent site for metastasis and is associated with lethal hemorrhagic complications [1]. Indeed, in the published literature, the prognosis is reported as poor due to the rapidity of tumor growth and association of bleeding risk with surgery, barotrauma, and acute respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Choriocarcinoma is a very rare malignant disease that is usually associated with a gestational event, such as hydatidiform mole, spontaneous abortion, or ectopic pregnancy [1]. Non-gestational choriocarcinoma is remarkably rare, arising from pluripotent germ cells in the gonads or midline structures, such as the mediastinum [2].…”
Section: Introductionmentioning
confidence: 99%